Exergy of Nano-Particulate Materials - Zevenhoven, Ron; Beyene, Asfaw (International journal of applied thermodynamics, 2014)
Nano-particle (NP) production processes may involve the use of significant amounts of complex chemicals. A more advanced approach for producing metallic NP materials may be the use of high voltage arc- or spark-driven systems. In addition to a reduction in chemicals use, the energy use of arcs/sparks exclusively in the form of electricity may be significantly less than the energy needs of waste stream processing from chemical usage, handling and post-treatment in nano-tech industry. Using exergy as a fundamental tool we assess the energy efficiency of NP material production, a subject obscured by lack of data and literature. One goal of this paper is to introduce a description of the exergy of NP materials and their processing. Silver, gold, copper, nickel, zinc and aluminium were taken as case studies. The results show that especially for NP material < 20 nm the surface energy of the material becomes significant. Moreover, a large energy penalty results from temperatures and enthalpies of NP condensation and solidification being lower than values for melting and evaporation of the bulk material. Comparing theoretical values with results from experiments shows that the specific electricity consumption is orders of magnitude higher than the energy penalties calculated as inevitable.